노인의 구강보건행위와 구강건강상태와의 관련성 조사 연구 - 권미영; Mi Young Gwon; 양진영; Jin Young Young (Chiwisaeng gwahakoeji, 2006)
This study set out to analyze the relationships between the senior citizens' dental health activities and dental health conditions, to provide basic data to develop a program for their better dental health, and finally to search for the ways to improve their life quality through dental health care. The subjects were 142 senior citizens(58 were male and 84 were female) who were 65 years old or older and visited a dental hospital or clinic in the Seoul metropolitan area from April 17 to April 28, 2006. With the cooperation from the dentists, the investigators examined their dental conditions and conducted one-on-one interviews to collect the information about their demographic characteristics, dental health activities, and subjective dental health conditions. The collected data were analyzed with T-test, ANOVA and Pearson's correlation coefficient using the SPSS WIN 11.5 program. The analysis results were summarized as follows: First, 58 men(40.8%) and 84 women(59.2%) consisted of the subject group, where percentage of the female participants was bigger Those who were aged from 65 to 69 made the biggest age group in the subjects, accounting for 58.5% with 83. Second, those who had three dental caries or less and then didn't treat them or treated them(F) accounted for the biggest percentage with 117(82.4%) and 72(50.7%) respectively. As for the remaining teeth, the biggest number of them(40 subjects, 28.2%) had three or less remaining. Third, it turned out the female subjects had a higher level of dental health activities than their male counterparts(P = 0.00). As for living expenses, those who were paid salary or earned income themselves carried out their dental health activities in a higher level than those who lived on the benefit from the government(p = 0.02). Fourth, the subjects' subjective dental health conditions had negative correlations with their dental caries not treated. And there were positive correlations between their dental caries not treated and dental caries lost and between their dental caries treated and remaining teeth. Fifth, those subjects who earned their living expenses themselves had the most dental caries treated at 5.4(p = 0.02), and there was statistically significant difference with the numbers. Sixth, those subjects who brushed their teeth in their own manner had 11.8 teeth lost(p = 0.05), which was more than the number of those who brushed their teeth in other methods. And there was statistically significant difference among them. The remaining teeth were found most at 17.3(p = 0.00) among those who brushed their upper and lower teeth separately. In addition, those who visited the public health center often had significantly more teeth treated(4.3) than others(p = 0.00). 본 연구는 수도권 치과병 의원에 내원한 65세 이상의 노인을 대상으로 구강보건행위와 구강건강상태를 파악한 후 보다 나은 삶의 질을 향상하기 위해서 노인의 구강건강증진 프로그램을 개발하는데 기초자료를 얻고자 시행하였다. 분석결과는 다음과 같다. 1. 본 연구의 대상은 남자 40.8%, 여자 59.2%로 여자가 남자보다 많은 비율을 차지했으며, 연령별로는 65세에서 69세가 58.5%로 가장 많았다. 2. 우식경험미처치치아와 우식경험처치치아는 3개 이하가 각각 82.4%, 50.7%로 가장 많았으며, 현존치아는 3개 이하가 28.2%로 가장 많이 나타났다. 3. 여자가 남자보다 구강보건행위의 수준이 높은 것으로 나타났으며(P = 0.00), 생활비 조달방법에서 정부보조금으로 생활을 하는 대상자보다 본인이 급여를 받거나 수입이 있는 대상자가 구강보건행위 수준이 높은 것으로 나타났다(p = 0.02). 4. 주관적 구강건강상태는 우식경험 미처치치아와 음의 상관관계를 보였고, 우식경험미처치치아와 우식경험상실치아, 우식경험처치치아와 현존치아는 양의 상관관계를 보였다. 5. 본인이 직접 생활비를 조달하는 노인들이 우식경험처치치아를 5.4개로 가장 많이 보유하고 있었으며(p = 0.02) 통계학적으로 유의한 차이를 보였다. 6. 잇솔질 방법에서 본인 마음대로 닦고 의 경우 상실치아가 11.8개(p = 0.05)로 다른 여러 가지 방법으로 잇솔질을 하고 있는 노인들에 비해 높게 나타났으며, 이는 통계적으로 유의한 차이를 보였다. 윗니와 아랫니를 따로 닦고 있다는 응답자에서 현존치아가 17.3개(p = 0.00)로 가장 많이 나타났으며, 또한 보건소를 자주 이용하는 노인들의 처치치아는 4.3개로 유의하게 많은 것으로 나타났다(p = 0.00). 이상의 결과를 종합하여 보면 65세 이상의 노인들은 대체적으로 구강건강상태가 양호한 것으로 나타났고, 특히잇솔질방법 등 올바른 구강건강행위를 하는 노인의 구강건강상태가 훨씬 양호하게 조사되었으며, 경제수준도 구강건강상태에 많은 영향을 미치는 것으로 조사되었다. 따라서 우리 치과위생사들은 노인들에게 구강건강을 증진시킬 수 있는 체계적인 노인구강보건교육이 이루어져야 하며, 지역자치단체에서는 노령인구를 위한 보건의료를 확장하여 보건소를 중심으로 적극적인 예방업무와 치료업무가 이루어지도록 치과의료서비스 접근도를 높이는 정책전환이 요구된다. 본 연구는 수도권 일부지역 치과병 의원에 내원한 환자들을 조사 대상자로 선정하였기에 조사기간 동안에 내원하지 않았거나 다른 진료기관을 이용한 노인들은 조사 대상에서 제외되어 우리나라 전체 노인의 구강건강실태를 대변하였다고 할수 없고, 구강검사시 치과병의원의 치과의사의 협조를 얻어 시행하였기에 평가자간의 오차가 다소 발생하여, 향후 검사의 오차를 줄일 수 있는 보다 체계적인 연구가 요망된다.